Kepastian Hukum Penggunaan Bukti Digital Berbasis Cloud Storage dalam Pembuktian Perkara Pidana - Ahmad Parhan; Aturkian Laia (INDO PUBLISHING, 2026)
The rapid development of cloud storage technology has transformed electronic data storage while creating new challenges for criminal evidence in Indonesia. This study analyzes the legal status of cloud storage-based digital evidence, legal certainty regarding its admissibility and evidentiary value, and the challenges associated with its use in criminal proceedings. The research employs a normative legal method using statutory and conceptual approaches based on the Indonesian Criminal Procedure Code, the Electronic Information and Transactions Law, the Personal Data Protection Law, and other relevant regulations. The findings indicate that cloud storage-based digital evidence has been legally recognized as an extension of admissible evidence. However, legal certainty remains limited due to the absence of specific rules governing evidence acquisition, authentication, chain of custody, and cloud forensics. Therefore, strengthening technical regulations, harmonizing legal frameworks, and enhancing international legal cooperation are essential to ensure legal certainty in criminal proceedings involving cloud-based digital evidence.